A Didactic Shift: Indigenous Studies Teaches an Italian Canadian about Being Italian - Piazza, Margherita (Rita) (Italian Canadiana)

(untitled) (Iter Press, 2022)
To Indigenous Nations, place is fundamental to one’s identity, language, and worldview. More than a geographical location, place reflects a sacred relationship that grounds them in their worldview of inclusivity, equity, and gratitude, and acts as a central role in the formation of identity. Eurocentric ideology is diametrically opposite to Indigenous values and beliefs. This is clearly evident in the Indian Act, a law designed to annihilate Indigenous languages and identity/culture and one that reflects the colonizer’s paternalistic and racist ideology. Both Italian Canadians and Indigenous Nations have experienced assimilation and acculturation. Both peoples have confronted the challenges of displacement. Yet, to fully live on this land and solidify our sense of belonging here, Italian Canadians have an obligation to be knowledgeable of Turtle Island’s colonial past and in doing so support Indigenous efforts to decolonize.